2020
DOI: 10.3390/en13123132
|View full text |Cite
|
Sign up to set email alerts
|

Using SCADA Data for Wind Turbine Condition Monitoring: A Systematic Literature Review

Abstract: Operation and maintenance (O&M) activities represent a significant share of the total expenditure of a wind farm. Of these expenses, costs associated with unexpected failures account for the highest percentage. Therefore, it is clear that early detection of wind turbine (WT) failures, which can be achieved through appropriate condition monitoring (CM), is critical to reduce O&M costs. The use of Supervisory Control and Data Acquisition (SCADA) data has recently been recognized as an effective solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 88 publications
0
66
0
1
Order By: Relevance
“…The survey is supported by an extensive list for up-to-date references. The present survey is intended to supplement many excellent reviews that address the prognostics of devices of contemporary vital importance [85,86,87,88,89,90,91,92,93,94].…”
Section: Resultsmentioning
confidence: 99%
“…The survey is supported by an extensive list for up-to-date references. The present survey is intended to supplement many excellent reviews that address the prognostics of devices of contemporary vital importance [85,86,87,88,89,90,91,92,93,94].…”
Section: Resultsmentioning
confidence: 99%
“…International Standards, such as IEC 61400-25 simplify the representation of turbines and guarantee the uniformity of information exchange and control design [ 5 ]. While initially designed for control purposes only, SCADA data have also predictive capabilities and it has been used widely in the literature [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In more recent works, the concept of a modern DT was outlined for application to aircraft and aerospace structures [4,5], and further reviews on the application of DT technology can be found in [6,7]. Studies [8][9][10][11][12][13] have discussed the development of a digital twin of wind turbines, structural health monitoring using Supervisory Control And Data Acquisition (SCADA) data and autonomous Unmanned Aerial Vehicles (UAVs), damage detection using an AI-assisted image process, and alternative algorithms for wind turbines. These studies [8][9][10][11][12][13] have contributed to bringing more autonomy, automation, and optimization into wind turbines, which increasingly grow in size and complexity.…”
Section: Introduction To the Bigger Picturementioning
confidence: 99%